Duplications of KIAA1549 and BRAF screening by Droplet Digital PCR from formalin-fixed paraffin-embedded DNA is an accurate alternative for KIAA1549 - BRAF fusion detection in pilocytic astrocytomas - Appay, Romain; Fina, Frédéric; Macagno, Nicolas; Padovani, Laëtitia; Colin, Carole; Barets, Doriane; Ordioni, Joanna; Scavarda, Didier; Giangaspero, Felice; Badiali, Manuela; Korshunov, Andrey; Pfister, Stefan; et al. (Modern pathology, 2018)
Pilocytic astrocytomas represent the most common glioma subtype in young patients and account for 5.4% of all gliomas. They are characterized by alterations in the RAS-MAP kinase pathway, the most frequent being a tandem duplication on chromosome 7q34 involving the BRAF gene, resulting in oncogenic BRAF fusion proteins. BRAF fusion involving the KIAA1549 gene is a hallmark of pilocytic astrocytoma, but it has also been recorded in rare cases of gangliogliomas, 1p/19q co-deleted oligodendroglial tumors, and it is also a common feature of disseminated oligodendroglial-like leptomeningeal neoplasm. In some difficult cases, evidence for KIAA1549-BRAF fusion is of utmost importance for the diagnosis. Moreover, because the KIAA1549-BRAF fusion constitutively activates the MAP kinase pathway, it represents a target for drugs such as MEK inhibitors, and therefore, the detection of this genetic abnormality is highly relevant in the context of clinical trials applying such new approaches. In the present study, we aimed to use the high sensitivity of Droplet Digital PCR (DDPCR™) to predict KIAA1549-BRAF fusion on very small amounts of formalin-fixed paraffin-embedded tissue in routine practice. Therefore, we analyzed a training cohort of 55 pilocytic astrocytomas in which the KIAA1549-BRAF fusion status was known by RNA sequencing used as our gold standard technique. Then, we analyzed a prospective cohort of 40 pilocytic astrocytomas, 27 neuroepithelial tumors remaining difficult to classify (pilocytic astrocytoma versus ganglioglioma or diffuse glioma), 15 dysembryoplastic neuroepithelial tumors, and 18 gangliogliomas. We could demonstrate the usefulness and high accuracy (100% sensitivity and specificity when compared to RNA sequencing) of DDPCR™ to assess the KIAA1549-BRAF fusion from very low amounts of DNA isolated from formalin-fixed paraffin-embedded specimens. BRAF duplication is both necessary and sufficient to predict this fusion in most cases and we propose that this single analysis could be used in routine practice to save time, money, and precious tissue.